Medical Cannabis for the Treatment of Migraine in Adults: A Review of the Evidence - Okusanya, Babasola O.; Lott, Breanne E.; Ehiri, John; McClelland, Jean; Rosales, Cecilia (Frontiers in Neurology, 2022)
Background Medical cannabis (MC) has been hypothesized as an alternative therapy for migraines, given the undesirable side effects of current migraine medications. The objective of this review was to assess the effectiveness and safety of MC in the treatment of migraine in adults. Methods We searched PubMed, EMBASE, PsycINFO, CINAHL, and Web of Science for eligible studies in adults aged 18 years and older. Two reviewers independently screened studies for eligibility. A narrative synthesis of the included studies was conducted. Results A total of 12 publications involving 1,980 participants in Italy and the United States of America were included. Medical cannabis significantly reduced nausea and vomiting associated with migraine attacks after 6 months of use. Also, MC reduced the number of days of migraine after 30 days, and the frequency of migraine headaches per month. MC was 51% more effective in reducing migraines than non-cannabis products. Compared to amitriptyline, MC aborted migraine headaches in some (11.6%) users and reduced migraine frequency. While the use of MC for migraines was associated with the occurrence of medication overuse headaches (MOH), and the adverse events were mostly mild and occurred in 43.75% of patients who used oral cannabinoid preparations. Conclusions There is promising evidence that MC may have a beneficial effect on the onset and duration of migraine headaches in adults. However, well-designed experimental studies that assess MC's effectiveness and safety for treating migraine in adults are needed to support this hypothesis.